Impact of iron therapy on Mentzer index and red cell distribution width index in primary school children with iron deficiency anemia - Budi Andri Ferdian; Nelly Rosdiana; Bidasari Lubis (Paediatrica Indonesiana, 2009)
Background Iron deficiency anemia (IDA) remains a commonnutritional problem, especially in school-age children. Due tothe many examinations that are needed to be performed and the invasive gold standard procedure, an easy and simple alternative examination to diagnose IDA is needed.Objective To determine the impact of iron therapy on Mentzerand red cell distribution width (RDW) indexes of children withIDA.Methods A randomized open clinical trial was conducted inprimary school aged children in North Aek Nabara, betweenNovember 2006 and November 2007. IDA was determined basedon WHO criteria. Subjects with severe anemia were excluded.Subjects were randomly assigned to groups that received eitheriron therapy or a placebo.Results Three-hundred subjects from aged 9 to 12 years oldwere recruited and 104 subjects completed the study. The meanRDW index of the iron and placebo groups after three monthsobservation were 239.96 (SD 39.25) and 235.17 (SD 31.77),respectively. The mean Mentzer index mean for the iron therapyand placebo groups after three months observation were 16.08(SD 1.98) and 16.20 (SD 2.27), respectively.Conclusion After therapy, there are no significant differences ineither the Mentzer or RDW indexes between the therapy andplacebo groups.